MULTIMEDIA BASED APPLICATION DESIGN OF SELECTION EXAMINATION AS A SUPPORT FOR PAPERLESS OFFICE IN PPKD EAST JAKARTA - Septanto, Henri; Ananto, Petrus Dwi (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Selection test potential trainees an early stagethat must be passed by the prospectivetrainees PPKD Vocational ComputerOperator in East Jakarta . If they pass the testof selection then they will be declaredacceptable in Vocational Computer OperatorPPKD East Jakarta . Exam selection ofparticipants aimed to screen potentialparticipants vocational training ComputerOperator to produce the trainees who have theability to match qualifications set by PPKDEast Jakarta.Selection is done through two kinds of tests,the first test on paper contains questionsabout the basic knowledge of the computerafter it conducted the interview. Applicationdesign exam multimedia-based selection wemade is aimed at reducing the use of paper atthe reception the selection of trainees so thatthe concept of paperless office that has beensocialized can also be applied in East JakartaPPKD albeit merely in vocational ComputerOperatorApplication design exam multimedia -basedselection is expected to bring some positiveimpacts, among others, about the inspectionsaves time and also save paper exams andanswer sheets, further away from the examapplication design multimedia-basedselection can help preserve nature because itsaves material usage raw paper derived fromnature that the trees in the forest.Keywords: Aplication Design, SelectionExamination, multimedia, paperless office